An Upgraded, Highly Saturated Linkage Map of Japanese Plum (Prunus salicina Lindl.), and Identification of a New Major Locus Controlling the Flavan-3-ol Composition in Fruits - Battistoni, Benjamín; Salazar, Juan; Vega, Wladimir; Valderrama-Soto, Diego; Jiménez-Muñoz, Pablo; Sepúlveda-González, Ailynne; Ahumada, Sebastián; Cho, Isaac; Gardana, Claudio Sebastiano; Morales, Héctor; Peña-Neira, Álvaro; Silva, Herman; et al. (Frontiers in Plant Science, 2022)
Japanese plum fruits are rich in phenolic compounds, such as anthocyanins and flavan-3-ols, whose contents vary significantly among cultivars. Catechin (C) and epicatechin (EC) are flavan-3-ol monomers described in the fruits of this species and are associated with bitterness, astringency, antioxidant capacity, and susceptibility to enzymatic mesocarp browning. In this study, we aimed to identify quantitative trait loci (QTL) associated with the content of flavan-3-ol in Japanese plum fruits. We evaluated the content of C and EC in the mesocarp and exocarp of samples from 79 and 64 seedlings of an F1 progeny (<‘98–99’ × ‘Angeleno’>) in the first and second seasons, respectively. We also constructed improved versions of linkage maps from ‘98–99’ and ‘Angeleno,’ presently called single-nucleotide polymorphisms (SNPs) after mapping the already available GBS reads to Prunus salicina Lindl. cv. ‘Sanyueli’ v2.0 reference genome. These data allowed for describing a cluster of QTLs in the cultivar, ‘Angeleno,’ associated with the flavan-3-ol composition of mesocarp and exocarp, which explain up to 100% of the C/EC ratio. Additionally, we developed a C/EC metabolic marker, which was mapped between the markers with the highest log of odds (LOD) scores detected by the QTL analysis. The C/EC locus was located in the LG1, at an interval spanning 0.70 cM at 108.30–108.90 cM. Our results suggest the presence of a novel major gene controlling the preferential synthesis of C or EC in the Japanese plum fruits. This study is a significant advance in understanding the regulation of synthesizing compounds associated with fruit quality, postharvest, and human health promotion.